Application of Digital Marketing to UMKM Grind Now Slow Bar in Using Social Media and E-Commerce - Edy Yulianto Putra; Jason (EQUATOR SINAR AKADEMIA, 2022)
In general, there are still some MSMEs that use social media only as a medium for posting photos, without further study in using social media. The purpose of carrying out community service activities is to help Grind Now Slow Bar SMEs who are facing problems such as the lack of people in Batam City knowing the location of the cafe and lack of time in making videos and designs to promote their products. Then, these MSMEs need a promotion strategy in digital marketing through advertising on Instagram social media, and e-commerce such as Gofood and Grab food. The results of these activities are to increase visitors increase followers from Instagram social media and increase turnover in these SMEs. Therefore, the author advises MSME owners to continue to improve and develop digital marketing so that it continues to grow.